2017
DOI: 10.2174/1874357901710011001
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Hepatitis B Virus Infection in the Age Range of 20-39 Years Old Individuals in Lome

Abstract: Background:Hepatitis B is a liver infection caused by the hepatitis B virus (HBV). It affects all women and men irrespective of age. Although sub-Saharan Africa is an area of high prevalence of this disease, data on the prevalence of acute and chronic HBV infections in this region remain to be widely documented.Objective:This study aimed to investigate the prevalence of HBV in relation to age in Centre Hospitalier Universitaire Campus (CHU-C), one of the two teaching hospitals of Lome, Togo.Method:The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 27 publications
(36 reference statements)
7
17
1
2
Order By: Relevance
“…In this study, the overall seropositivity of HBV infection was 6.4%, with rst time donors recording a seropositivity of 8.8%. This "high intermediate category" observation on the overall seropositivity is lower than the reports of studies in other African countries including Ghana (7.5% and 13.3%), Equatorial Guinea (10.01%), Cameroon (12.6%),Burkina Faso (14.47%), and Togo (19.08%) [9,[14][15][16][17][18]. Our ndings are, nonetheless, higher than the recorded seroprevalence of 4.1% and 3.21 that was reported in respectively, Northwest Ethiopia and Madagascar (19)(20).…”
Section: Discussionmentioning
confidence: 58%
“…In this study, the overall seropositivity of HBV infection was 6.4%, with rst time donors recording a seropositivity of 8.8%. This "high intermediate category" observation on the overall seropositivity is lower than the reports of studies in other African countries including Ghana (7.5% and 13.3%), Equatorial Guinea (10.01%), Cameroon (12.6%),Burkina Faso (14.47%), and Togo (19.08%) [9,[14][15][16][17][18]. Our ndings are, nonetheless, higher than the recorded seroprevalence of 4.1% and 3.21 that was reported in respectively, Northwest Ethiopia and Madagascar (19)(20).…”
Section: Discussionmentioning
confidence: 58%
“…That association was found in a survey in northern Uganda where females were more infected than males [19]. A previous study in Lomé reported that men were more infected than women [20].…”
Section: Discussionmentioning
confidence: 59%
“…Many studies have already reported a higher prevalence of HBV in men compared to women [13] [20] [21]. In Lemoine's study, the prevalence of hepatitis B among men was 10.5% compared to 7.6% among women (p = 0.004).…”
Section: Discussionmentioning
confidence: 93%
“…One study conducted among people living with HIV in 2011 estimated the HBV prevalence at 9.7% [4]. Another study among prisoners in 2013 estimated the prevalence at 12.5%, while a study among individuals in a hospital in Lomé found a prevalence as high as 19.1% [5] [13]. However, no study in Togo has so far specifically focused on the prevalence of HBV among youth and university students, who could be considered a vulnerable population.…”
Section: Introductionmentioning
confidence: 99%